2015
DOI: 10.1088/0029-5515/55/10/104012
|View full text |Cite
|
Sign up to set email alerts
|

Overview of the RFX-mod contribution to the international Fusion Science Program

Abstract: The RFX-mod device is operated both as a reversed field pinch (RFP), where advanced regimes featuring helical shape develop, and as a tokamak. Due to its flexibility, RFX-mod is contributing to the solution of key issues in the roadmap to ITER and DEMO, including MHD instability control, internal transport barriers, edge transport and turbulence, isotopic effect, high density limit and three-dimensional (3D) non-linear MHD modelling. This paper reports recent advancements in the understanding of the self-organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 45 publications
1
11
0
Order By: Relevance
“…The non-adiabatic response h s derived from the gyrokinetic equation for ions in a RFP configuration satisfies [39] The integral dispersion equation for study of ITG modes in toroidal RFP plasmas is extended to include a second (impurity) ion species [32]. Hydrogen ions are referred as main ion species, while all the rest subdominant ion species, such as carbon, oxygen, lithium and boron, are referred as impurity ions in the real RFX-mod experiment [40][41][42]. The full kinetic characteristics, including finite Larmor radius, magnetic gradient and curvature drifts, of the main and impurity ions are taken into account.…”
Section: Physics Model and Dispersion Equationmentioning
confidence: 99%
“…The non-adiabatic response h s derived from the gyrokinetic equation for ions in a RFP configuration satisfies [39] The integral dispersion equation for study of ITG modes in toroidal RFP plasmas is extended to include a second (impurity) ion species [32]. Hydrogen ions are referred as main ion species, while all the rest subdominant ion species, such as carbon, oxygen, lithium and boron, are referred as impurity ions in the real RFX-mod experiment [40][41][42]. The full kinetic characteristics, including finite Larmor radius, magnetic gradient and curvature drifts, of the main and impurity ions are taken into account.…”
Section: Physics Model and Dispersion Equationmentioning
confidence: 99%
“…The aim of this paper is to characterize the response of the edge plasma to a 3D magnetic field with several helicities (resonant and non-resonant) in the RFX-mod experiment (R = 2 m, a = 0.459 m), operated both in reversed field pinch (RFP) and tokamak configurations [7,8]. It will be shown that the edge pressure, floating potential and perpendicular flow follow the temporal and spatial structure of the MP only as a first approximation: even if an almost monochromatic m = 1 MP is applied, the poloidal modulation of the plasma edge is characterized by sidebands, which reflect the complex (and not monochromatic) structure of the magnetic connection length to the wall.…”
mentioning
confidence: 99%
“…Even though the toroidal experiment has been designed to operate in reversed field pinch configuration, thanks to an easily reconfigurable winding and power supply systems and to a very flexible control system, RFX-mod operated also as a low plasma current (I p < 150 kA) Tokamak. Several experimental campaigns related to low-q (q edge < 2) operations [17], sawtoothing mitigation and runaway decorrelation through 3D applied perturbations [18,19], L-H transition in circular and D-shaped plasmas [20], have been successfully run.…”
Section: Rfx-mod2mentioning
confidence: 99%